2017
DOI: 10.3171/2017.1.spine16352
|View full text |Cite
|
Sign up to set email alerts
|

Anterior lumbar discectomy and fusion for acute cauda equina syndrome caused by recurrent disc prolapse: report of 3 cases

Abstract: There is a lack of information and consensus regarding the optimal treatment for recurrent disc herniation previously treated by posterior discectomy, and no reports have described an anterior approach for recurrent disc herniation causing cauda equina syndrome (CES). Revision posterior decompression, irrespective of the presence of CES, has been reported to be associated with significantly higher rates of dural tears, hematomas, and iatrogenic nerve root damage. The authors describe treatment and outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The recovery in CES may take months to years, as reported conventionally 3 , 31 . A three-case report of anterior lumbar surgery and another report of endoscope assisted OLIF (Oblique lumbar Interbody Fusion) in CES, report a dramatic quick recovery in bladder function 32 , 33 . Although these are relatively open surgery, this should raise a prudent question of an underestimated manipulative injury in posterior surgeries.…”
Section: Discussionmentioning
confidence: 96%
“…The recovery in CES may take months to years, as reported conventionally 3 , 31 . A three-case report of anterior lumbar surgery and another report of endoscope assisted OLIF (Oblique lumbar Interbody Fusion) in CES, report a dramatic quick recovery in bladder function 32 , 33 . Although these are relatively open surgery, this should raise a prudent question of an underestimated manipulative injury in posterior surgeries.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, when considering surgical intervention for this specific pathology of the lumbar spine, Tan et al reported three successful cases of patients who suffered from CES who were successfully treated via the anterior approach with lumbar discectomy [17]. However, regardless of approach, early intervention for patients with complete or incomplete CES is necessary and associated with successful clinical outcomes with minimal neurological loss [18].…”
Section: Discussionmentioning
confidence: 99%